VALIDITY AND PRACTICALITY OF STEM-PBL BASED THERMOCHEMISTRY TEACHING MATERIALS FOR CHEMISTRY EDUCATION STUDENTS - Dwy Puspita Sari; Mutiara Agustina Nst; Dewi Syafriani; Alfira Julian Pratiwi (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2026)
This study aimed to develop STEM-PBL-based thermochemistry teaching materials and examine their validity and practicality for use in chemistry education. This research employed a Research and Development (R&D) approach using the ADDIE model, limited to the Analysis, Design, and Development stages. Following product development, expert validation and a limited practicality assessment were conducted. The research subjects consisted of three expert validators and 30 students from the Chemistry Education Study Program. The instruments used were validity and practicality questionnaires employing a four-point Likert scale. Validity data were analyzed using average validation scores, while practicality data were analyzed using the percentage of student responses. The results showed that the developed teaching materials obtained an average validity percentage of 93%, categorized as highly valid. The practicality assessment yielded a percentage score of 92%, categorized as highly practical. Students responded positively to the developed teaching materials, indicating that they were easy to use, attractive, and beneficial for supporting thermochemistry learning activities. The practicality assessment was limited to student responses and did not evaluate learning effectiveness. Therefore, the STEM-PBL-based thermochemistry teaching materials are considered highly valid and highly practical for use in chemistry education.